2023
DOI: 10.14716/ijtech.v14i3.6000
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Hydrodynamic Performance Analysis of a Shell and Tube Heat Exchanger Using the AHP Multicriteria Method

Karol Yuliete Ravelo-Mendivelso,
Mercy Tatiana Villate-Fonseca,
José Daniel Hernández-Vásquez
et al.

Abstract: The goal of this work is to identify the best alternatives that allow for improving the thermal efficiency of a shell and tube heat exchanger in real operating conditions. The main motivation for carrying out the research is based on the need identified, together with the oil, natural gas, and alternative energy industry, to analyze and learn about the main criteria that directly impact the thermal efficiency of a heat exchanger. The applied methodology was based on the AHP (Analytic Hierarchy Process) multicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…According to the results, the Safety of Life at Sea (SOLAS) and Fire Safety Systems (FSS) were identified as the top priorities for regulation in almost all countries. Research by Ravelo-Mendivelso et al (2023) that was based on the AHP (Analytic Hierarchy Process) multi-criteria method identified the best alternatives to improve the thermal efficiency of the housing and the shell heat exchanger under actual operating conditions. A key motivation for conducting research based on identified needs, in partnership with oil, natural gas, and alternative energy industries, is to analyze and understand the key criteria that directly impact the thermal performance of heat exchangers.…”
Section: Ship Detention Under Port State Control (Psc) Inspectionmentioning
confidence: 99%
“…According to the results, the Safety of Life at Sea (SOLAS) and Fire Safety Systems (FSS) were identified as the top priorities for regulation in almost all countries. Research by Ravelo-Mendivelso et al (2023) that was based on the AHP (Analytic Hierarchy Process) multi-criteria method identified the best alternatives to improve the thermal efficiency of the housing and the shell heat exchanger under actual operating conditions. A key motivation for conducting research based on identified needs, in partnership with oil, natural gas, and alternative energy industries, is to analyze and understand the key criteria that directly impact the thermal performance of heat exchangers.…”
Section: Ship Detention Under Port State Control (Psc) Inspectionmentioning
confidence: 99%